2018
DOI: 10.1159/000501464
|View full text |Cite
|
Sign up to set email alerts
|

Public Understanding and Opinions regarding Genetic Research on Alzheimer’s Disease

Abstract: Background: Participants willing to provide genetic samples are needed to propel the science of Alzheimer's disease (AD) treatment and prevention forward. Limited public understanding of what AD genetic research entails and participation concerns may serve as recruitment challenges. Objective: This study seeks to understand how well older adults understand AD genetic research and if understanding relates to concerns about participation or willingness to engage. Methods: Surveys included a mock AD consent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Further, onset of symptoms can be delayed and managed by lifestyle changes. The utilization of knowledge relating to human genetics is desired in public health services for disease prevention and health management, and may enable reduction of healthcare costs [ 42 , 43 ]; good effects have already been seen as a result of screening of some genetic disorders [ 44 ] and genetic testing for Alzheimer’s disease [ 45 ]. The results of our short-term education program suggested that it may also indirectly contribute to those ethical aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Further, onset of symptoms can be delayed and managed by lifestyle changes. The utilization of knowledge relating to human genetics is desired in public health services for disease prevention and health management, and may enable reduction of healthcare costs [ 42 , 43 ]; good effects have already been seen as a result of screening of some genetic disorders [ 44 ] and genetic testing for Alzheimer’s disease [ 45 ]. The results of our short-term education program suggested that it may also indirectly contribute to those ethical aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts have been made to make students more aware of how genetics is a part of their everyday lives [ 29 ]. Genetics can be used to predict hyperlipidemia in children and to prevent heart disease [ 30 , 31 ]. It also contributes to the treatment of Alzheimer’s disease [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Genetics can be used to predict hyperlipidemia in children and to prevent heart disease [ 30 , 31 ]. It also contributes to the treatment of Alzheimer’s disease [ 31 ]. The use of genetic testing for finding risks (for example, hyperlipidemia and cancer, among others) has increased the contribution of genetics to public health [ 30 , 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation